Parvovirus B19 detected in Rosai–Dorfman disease in nodal and extranodal manifestations. Issue 12 (1st December 2006) - Mehraein, Y; Wagner, M; Remberger, K; Füzesi, L; Middel, P; Kaptur, S; Schmitt, K; Meese, E
Abstract : Sinus histiocytosis with massive lymphadenopathy (SHML), also designated as Rosai–Dorfman disease (RDD), is a rare benign reactive lymphoproliferative disorder. It is defined by a characteristic histopathology with sinus histiocytosis and haemophagocytosis known as emperipolesis. In histiocytes S100 is strongly expressed, whereas CD1a staining typically is negative. The disease mainly manifests at a single lymph node; however, multilocular and extranodal affection can occur. Causative infectious agents, and virus infections in particular, have repeatedly been suspected, although until now the origin of the disease has been unclear. Four cases of RDD (two nodal sites and two extranodal upper respiratory tract sites) were analysed for parvovirus B19 (B19) infection by immunohistochemistry to detect B19 capsid proteins VP1/VP2. In all the four cases, huge numbers of B19-positive cells were partly detected. The positive cells were identified either as lymphocytes or, in one extranodal case, also as respiratory epithelial cells. This is the first report of B19 infection in RDD tissue, indicating that B19 may be associated with the pathogenesis of SHML.